2013
DOI: 10.1155/2013/948783
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Experimental Preconditioning Using Vascular Endothelial Growth Factor in Stroke and Subarachnoid Hemorrhage

Abstract: Vascular endothelial growth factor (VEGF) stimulating angiogenesis was shown to be a potential novel therapeutic approach for the treatment of ischemic vascular diseases. The goal of the present study was to examine whether transfection of VEGF before occurrence of major stroke (part I) and cerebral vasospasm after experimental subarachnoid hemorrhage (SAH; part II) develops neuroprotective qualities. A total of 25 (part I) and 26 (part II) brains were analyzed, respectively. In part one, a significant reduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“… 8 Another possibility – though not mutually exclusive from HIF-1 α 's effects on vascular ECs – is that one or more HIF-1 α -driven secreted proteins exert paracrine protective effects on neighboring cells. Potential target molecules here include iNOS (which, as mentioned above, has been implicated in the vascular protection afforded by isoflurane in cerebral ischemia 45 ) and vascular endothelial growth factor (which has been previously linked to vasospasm protection 56 ). Third is the neurovascular protection afforded by postconditioning present across SAH model systems (endovascular perforation, cisterna magna injection, prechiasmatic injection), species (lissencephalic vs. gyrencephalic), gender (male vs. female), age (young vs. old), comorbidities (hypertension, diabetes, etc.…”
Section: Discussionmentioning
confidence: 99%
“… 8 Another possibility – though not mutually exclusive from HIF-1 α 's effects on vascular ECs – is that one or more HIF-1 α -driven secreted proteins exert paracrine protective effects on neighboring cells. Potential target molecules here include iNOS (which, as mentioned above, has been implicated in the vascular protection afforded by isoflurane in cerebral ischemia 45 ) and vascular endothelial growth factor (which has been previously linked to vasospasm protection 56 ). Third is the neurovascular protection afforded by postconditioning present across SAH model systems (endovascular perforation, cisterna magna injection, prechiasmatic injection), species (lissencephalic vs. gyrencephalic), gender (male vs. female), age (young vs. old), comorbidities (hypertension, diabetes, etc.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, by analysing the cerebrovascular microperfusion, vasospasm induction was observed immediately after the SAH incident. The increase in the concentration of VEGF-A was also observed, which is associated with neoangiogenesis increase in cerebral vessels [29].…”
Section: Discussionmentioning
confidence: 99%
“…So far two receptors specific for VEGF: VEGFR-1 (Flt1) and VEGFR-2 (KDR/Flt-1), have been identified. Most effects at the cellular level result from interaction of VEGFR-2 receptor with its ligand VEGF-A [17, 18]. VEGF-A is produced by T lymphocytes, macrophages, and platelets.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation